A review of possible mechanisms for mercury migration in diagenesis: Clay to pyrite - Xu, Huan; Ran, Bo; Liu, Shugen; Sun, Tong; Luo, Chao; Li, Yi; Zhu, Yiqing (Frontiers in Earth Science, 2023)
Though sedimentary mercury in marine sediments has been regarded as a geological indicator of volcanic activity based on volcanism activity is the dominant natural source of Hg to the oceans, the influence of diagenesis on mercury cannot be dismissed. Marine mudstone has been selected to explore the migration of mercury from the syn-sedimentary stage to the diagenetic stage in this review. Marine mudstones undergo a series of significant transformation processes, including the illitization of smectite and the formation of framboidal pyrite aggregates during the diagenetic stage. This process makes the adsorption capacity of minerals change significantly that clay minerals are weakened, while pyrites are enhanced. In this reason, it is inferred that the sedimentary mercury may re-migrate from clay minerals to pyrite. This at least means that the indication of volcanic activity by mercury enrichment in marine mudstone need to be re-evaluated.